Pemberdayaan KWT Citra Lestari Melalui Pelatihan Pengolahan Jahe Menjadi Serbuk Jahe di Dukuh Jurugan Desa Karangpatihan Kecamatan Pulung Kabupaten Ponorogo - Yoga Tri Ambudi; Ibnu Muchlis (Social Science Academic, 2025)
Kwt Citra Lestari is a form of farmer organization whose members consist of women who are involved in agricultural activities. This group is located in Jurugan Hamlet Karangpatihan Village, Pulung District, Ponorogo Regency. The backgorund of this research is that the problem faced is that KWT Citra Lestari in the past few months has experienced a decline in activities or you colud say it is Fakum. In this study, the method used was Asset Based Community Development (ABCD), KWT Citra Lestari has ginger powder will be managed by the Citra Lestari Women Farmers Group. The result of holding this training is that KWT Citra Lestari members can understand and understand processing so that they can develop and have additional income. This training aims to add to KWT Citra Lestari’s activities, develop the potential of ginger as an instant drink, increase knowledge, productivity and skills creativity and the main objective is to create new KWT Citra Lestari MSME products.